The Popularity of Wayang Orang Sriwedari During the Dutch East Indies Period: Reviews of Dutch Newspapers in 1923-1938 - Herlambang, Rudy Wicaksono; Purwasito, Andrik; ., Warto; Widayat, Rahmanu (Journal of Posthumanism, 2025)
Wayang Orang Sriwedari which is one of the cultural theatrical arts in Surakarta City has put an impact on every era, including at its peak which encompasses its historical side. Founded in the early 20th century, Wayang Orang Sriwedari appeared at the same time as the inauguration of Sriwedari Park at the heart of Surakarta city around 1901. This essay is aimed to describe the romanticization of the history of Wayang Orang Sriwedari during the Dutch East Indies era by reviewing a number of archives of Dutch-language newspapers, ranging from De Locomotief, De Nieuwe Vorstenlanden, Het volk: dagblad voor de arbeiderspartĳ, Nieuwe Haarlemsche courant to Soerabaijasch handelsblad which were announced and reported the popularity of Wayang Orang Sriwedari around 1923-1938. This study seeks to expose the Dutch archives into Indonesian historiography, especially in revealing the romanticization of history of the popularity of Wayang Orang Sriwedari that are struggling in a number of difficult times from the land dispute of Sriwedari Park to the COVID-19 pandemic which has made them pause for a while and adopt new habits. This article provides a different view on the colonial record that had popularized Wayang Orang Sriwedari until achieving its popularity in Java and the Dutch East Indies, although this popularity resulted in several negative impacts.